İğne deliği fotoğraf ve çağdaş kullanımı - Bilgin, Aydın Berk (My University, 2012)
İĞNE DELİĞİ FOTOĞRAF VE ÇAĞDAŞ KULLANIMI Fotoğraf yapısABSTRACT PİNHOLE PHOTOGRAPHY AND CONTEMPORARY USES Photo structurally with the aid of a machine, within certain limits the two-dimensional images created on flat surfaces occur in a certain measure. The most basic technique to create a pinhole image of a machine and therefore do not depend on the specific surface and the limits of measurement is able to produce images. The wealth owned by a small number of technical terms that are preferred by the individual photographers and photo fancier. The simple structure of the primitive form of the technique and the recognition of its wrong and leads to the formation of prejudices. This is what is working with the pinhole technique, is explained by what can be done. Sufficiently understood the technique has been observed during the research process. Working with the technique is not an ordinary device, as well as the simplicity of the required special needs, take advantage of this technique are given in the contributions of artists to the art of photography with a variety of production. al olarak bir makine yardımı ile belli sınırlar dâhilinde iki boyutlu düz yüzeylerde belli ölçü sınırlarında oluşturulan görüntülerden meydana gelmektedir. Görüntü oluşturmanın temel yolu olan iğne deliği bir makineye ve dolayısıyla belirli yüzey ve ölçü sınırlarına bağlı kalmadan fotoğraf üretebilmektedir. Teknik sahip olduğu zenginlik açısından çok az sayıda ki fotoğraf sanatçısı ve fotoğraf meraklısı birey tarafından tercih edilmektedir. Tekniğin basit yapısı ve ilkel formu onun yanlış tanınmasına ve ön yargıların oluşmasına yol açmaktadır. Bu çalışma ile iğne deliği tekniğinin ne olduğu, neler yapılabileceği hakkında bilgi verilmiştir. Araştırma sürecinde tekniğin yeterince anlaşılmadığı gözlemlenmiştir. Çalışma ile tekniğin sıradan bir araç olmadığı, basitliğinin yanı sıra ihtiyaç duyulan özel gereksinimlerine, bu teknikten faydalanan sanatçıların üretim çeşitliliği ile fotoğraf sanatına katkılarına yer verilmiştir.
Keywords: Fotoğrafçılık